2010
DOI: 10.1007/s10661-010-1574-5
|View full text |Cite
|
Sign up to set email alerts
|

Alkylphenols and polycyclic aromatic hydrocarbons in eastern Mediterranean Spanish coastal marine bivalves

Abstract: This paper reports the first results on alkylphenol pollution in edible bivalves from the Spanish coast. Two sampling campaigns (July 2006 and July 2007) were carried out to determine the concentration of nonylphenol (NP), octylphenol (OP) and eight Polycyclic Aromatic Hydrocarbons (PAHs) in wild mussels (Mytilus Galloprovincialys) and clams (Donax trunculus) at 14 sampling sites along the eastern Mediterranean Spanish coast. The results show that NP is the predominant alkylphenol, being the port of Valencia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Fluoranthene was selected as (i) it is a model PAH belonging to the list of priority substances in water policy of the European Commission (Directive 2008/105/EC) and (ii) it constitutes one of the most abundant PAH found in the aquatic environment and in molluscs (Baumard et al, 1998;Bouzas et al, 2011). It is noteworthy that in most of the cited studies, as well as in our work, animals were acclimatized and then reared in "clean water" (seawater filtered on active carbon filters in our case) and exposures were performed in clean and controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoranthene was selected as (i) it is a model PAH belonging to the list of priority substances in water policy of the European Commission (Directive 2008/105/EC) and (ii) it constitutes one of the most abundant PAH found in the aquatic environment and in molluscs (Baumard et al, 1998;Bouzas et al, 2011). It is noteworthy that in most of the cited studies, as well as in our work, animals were acclimatized and then reared in "clean water" (seawater filtered on active carbon filters in our case) and exposures were performed in clean and controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…FLU, a three-aromatic-ring PAH, is considered to be the most toxic PAH for marine biota in the short term (Ben Othman et al, 2012) and it is one of the PAHs found in highest concentrations in sediments, particulate matter, and water (Baumard et al, 1998;Van Hattum et al, 1998;Viñas et al, 2010). It has a persistent lipophilic character, compared to other compounds of the same group, and consequently, it is one of the most abundant PAHs accumulated in molluscs (Baumard et al, 1998;Bouzas et al, 2011;Bellas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide annual alkylphenol production was estimated to be 500,000 t and increasing in 1997 (Ying 2006), and a large proportion of this material ends up in aquatic or marine environments via discharge from wastewater treatment plants or industry (Soares et al 2008, David et al 2009, Harman et al 2011. Alkylphenol contamination has been reported widely in both freshwater (Soares et al 2008) and marine (David et al 2009) ecosystems, particularly in sediments and filter-feeding organisms (e.g., Hale et al 2000, Munshi et al 2009, Bouzas et al 2011. Alkylphenols were also detected in the urine of 95% of humans tested in 2004 (Calafat et al 2005).…”
Section: Introductionmentioning
confidence: 99%